Necroptosis Underlies Hepatic Damage in a Piglet Model of Lipopolysaccharide-Induced Sepsis - Xu, Qiao; Guo, Junjie; Li, Xiangen; Wang, Yang; Wang, Dan; Xiao, Kan; Zhu, Huiling; Wang, Xiuying; Hu, Chien-An Andy; Zhang, Guolong; Liu, Yulan (Frontiers in Immunology, 2021)
Background: Necroptosis is a newly recognized form of programmed cell death with characteristics of both necrosis and apoptosis. The role of necroptosis in hepatic damage during sepsis is poorly understood. In this study, we investigated the occurrence of necroptosis in hepatic damage, and its contribution to hepatic damage in a piglet model of lipopolysaccharide (LPS)-induced sepsis. Methods: Two animal experiments were conducted. In trial 1, piglets were challenged with LPS and sacrificed at different time points after LPS challenge. In trial 2, piglets were pretreated with necrostatin-1, a specific inhibitor of necroptosis, prior to LPS challenge. Alterations in the hepatic structure and function, pro-inflammatory cytokine expression, and the necroptosis signaling pathway were investigated. Typical ultrastructural characteristics of cell necrosis was observed in the liver of LPS-challenged piglets. Results: Expressions of critical components of necroptosis including kinases (RIP1, RIP3, and MLKL), mitochondrial proteins (PGAM5 and DRP1), and an intracellular damage-associated molecular pattern (HMGB1) were increased in the liver in a time-dependent manner, followed by hepatic inflammation, morphological damage, and dysfunction as manifested by elevated hepatic expression of IL-1β, IL-6 and TNF-α as well as increased serum AST and AKP activities and the AST/ALT ratio. Pretreatment with necrostatin-1 significantly reduced the expression of RIP1, RIP3 and MLKL as well as PGAM5, DRP1 and HMGB1, which subsequently led to obvious attenuation of hepatic inflammation and damage. Conclusions: Our study demonstrates that necroptosis occurs in the liver during sepsis and contributes to septic hepatic injury.